Survival of patients with malignant tumors of the eye by sex, age and histological structure of neoplasms - Vakhtang Merabishvili; El’vira Merabishvili (Oftalʹmologiâ, 2016)
Introduction. The main criterion for evaluating the efficiency of oncology service at the population level should be survival of cancer patients under strict control of all stages of conducted research from the collection of primary medical documentation to careful monitoring the state of health of follow-up patients. In the previous article («Russian ophthalmology» № 2, 2012) we have followed survival dynamics in patients with malignant tumors of the eye (C69) and C69.3 for the period from 1994 to 2008 in comparison with the European average data (programs Eurocare-3 and Eurocare-4).Purpose. To continue the study of the dynamics of the observed and relative survival in patients with malignant tumors of the eye and its adnexa (C69) at the population level taking into account the peculiarities of this process in respect to tumors of choroid (S64.3). Material and methods. Since the formation of Cancer Registry’s database, from 1994 to 2012 there were registered 750 cases for the entire column C69, including 395 cases of malignant tumors of the choroid. The paper presents a detailed histological structure of malignant tumors per C69 and C 69.3. Survival rates were estimated for all histological codes. Estimations were carried out according to classical methods of data analysis at the population-based level.Results. The findings suggest certain stabilization of efficiency of specialized care to patients with malignant eye tumors. This same applies to the structure of histological tumor types.Conclusions. This study confirms constant positive dynamics of survival in patients with malignant tumors of the eye and its adnexa.